Method and device for uniformly coating catalyst particles on surface of carbon fiber
Through the combination of high-temperature glue removal method, electrochemical anodization method, electroplating method and chemical vapor deposition method, the problems of uneven distribution of catalyst particles and inaccurate growth control of carbon nanotubes are solved, and the uniform distribution of catalyst particles and the uniform growth of carbon nanotubes are achieved, which improves the accuracy and consistency of the growth process.
Patent Information
- Application Number
- CN202510126814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-05-02
AI Technical Summary
The prior art has shortcomings in the problems of uneven distribution of catalyst particles and inaccurate control of carbon nanotube growth, especially in terms of the accuracy and controllability of the distribution of catalyst particles.
The high-temperature glue removal method is used to remove the colloid on the surface of the carbon fiber, and then the carbon fiber surface is activated by electrochemical anodizing method. Then, the catalytic coating is applied based on the electroplating method to coat the catalytic plating layer, and finally carbon nanotubes are grown on the surface of the carbon fiber by chemical vapor deposition.
The uniform distribution of catalyst particles on the surface of carbon fiber is achieved, ensuring the uniform growth of carbon nanotubes on the surface of carbon fiber, and improving the accuracy and consistency of the growth process of carbon nanotubes.
Smart Images

Figure CN119913585A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of carbon fiber surface coating with catalysts, and in particular to a method and device for uniformly coating the surface of carbon fiber with catalyst particles. Background Art
[0002] At present, the method of coating a catalyst solution and then reducing it is widely used in the preparation of catalysts and the growth control of carbon nanotubes. However, this method has certain limitations, especially in the uniform distribution of catalyst particles. Since the catalyst particles are prone to form aggregates during the coating process of the catalyst solution, the distribution of catalyst particles on the substrate is uneven, thereby affecting the growth quality of carbon nanotubes. In addition, the growth process of carbon nanotubes is also affected by the size and uniformity of the catalyst particles. The uneven catalyst distribution will cause the growth rate of carbon nanotubes in different areas to be different, thereby affecting its overall performance.
[0003] In order to solve the problems of uneven distribution of catalyst particles and inaccurate control of carbon nanotube growth, the prior art has proposed some solutions. For example, the sol-gel method, chemical vapor deposition (CVD) technology and other methods are used to improve the uniformity of catalyst distribution. These methods obtain a more uniform distribution of catalyst particles by finely controlling parameters such as the concentration of the catalyst solution, coating technology or growth temperature. The sol-gel method can form a uniform catalyst film by controlling the precursor, while chemical vapor deposition uses gas catalytic reactions under high temperature conditions to promote the uniform deposition of catalysts. However, these methods still have some shortcomings, especially in terms of the accuracy and controllability of catalyst particle distribution. For example, although the sol-gel method can improve the catalyst distribution, it is often difficult to maintain high uniformity during large-scale preparation; although the chemical vapor deposition technology can provide a more uniform catalyst layer, the control of parameters such as temperature and atmosphere is more complicated, which easily leads to excessive or non-uniform deposition of the catalyst. In addition, these methods are also faced with the difficulty of controlling the size of catalyst particles, making it difficult to achieve precise orientation and controllability of the growth of carbon nanotubes.
[0004] Therefore, one or more methods are needed to solve the above problems.
[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0006] The purpose of the present disclosure is to provide a method and apparatus for uniformly coating catalyst particles on the surface of carbon fiber, thereby overcoming one or more problems caused by the limitations and defects of the related art at least to a certain extent.
[0007] According to one aspect of the present disclosure, there is provided a method for uniformly coating catalyst particles on the surface of a carbon fiber, comprising:
[0008] Use high temperature debonding method to decompose the glue remaining on the surface of carbon fiber by heating the carbon fiber to a preset high temperature;
[0009] The surface of the carbon fiber is pretreated by performing surface activation treatment on the carbon fiber after the colloid is removed using an electrochemical anodizing method;
[0010] Based on the electroplating method, current is passed through a pre-configured electroplating solution to coat the surface of the carbon fiber that has undergone surface pretreatment with a catalytic coating;
[0011] The carbon-containing gas is used as a carbon source, and the catalytic coating is used as a catalyst through a chemical vapor deposition method to complete the growth of carbon nanotubes on the surface of the carbon fiber.
[0012] In an exemplary embodiment of the present disclosure, the preset high temperature is 400-500 degrees Celsius.
[0013] In an exemplary embodiment of the present disclosure, the colloid remaining on the surface of the carbon fiber is decomposed by heating the carbon fiber to a preset high temperature, comprising:
[0014] Load the carbon fiber into a high-temperature sintering furnace and connect it to an argon gas line;
[0015] Expelling air from the high temperature sintering furnace by controlling the flow rate of argon gas to 0.4-0.6 liters per minute;
[0016] After the air in the high-temperature sintering furnace is exhausted, the temperature control program is started to adjust the debonding temperature to 400-500 degrees Celsius at a heating rate of 10 degrees Celsius per minute, and the temperature of 400-500 degrees Celsius is maintained for two hours, and the glue remaining on the surface of the carbon fiber is started to be decomposed.
[0017] In an exemplary embodiment of the present disclosure, the carbon fiber after the colloid is removed is subjected to surface activation treatment, comprising:
[0018] A 5% by mass ammonium dihydrogen phosphate solution is prepared as an electrolyte;
[0019] A DC regulated power supply with a current of 0.4A-0.6A and a voltage of 15V-20V is used as the power supply for the electrolytic cell;
[0020] The carbon fiber after the colloid is removed is set as the anode of the electrolytic cell, the platinum electrode is set as the cathode of the electrolytic cell, and the electrode distance is 9-11 cm;
[0021] The electrolysis time was set to 1 minute, and the electrolysis pretreatment of the carbon fiber surface was started.
[0022] In an exemplary embodiment of the present disclosure, the electroplating solution comprises components of nickel sulfate hexahydrate with a mass concentration of 260-280 g / L, nickel chloride of 65-75 g / L, boric acid of 35-45 g / L, and sodium dodecyl sulfate of 0.09-0.11 g / L.
[0023] In an exemplary embodiment of the present disclosure, the pH value of the electroplating solution is 3-4.
[0024] In an exemplary embodiment of the present disclosure, current is passed through a pre-configured electroplating solution to apply a catalytic coating to the surface of the carbon fiber that has undergone surface pretreatment, comprising:
[0025] A DC regulated power supply with a current of 0.3A-0.5A and a voltage of 17V-20V is used as an electroplating power supply;
[0026] The carbon fiber with surface pretreatment is set as the electroplating cathode, the platinum electrode is set as the electroplating anode, and the electrode distance is 9-11 cm;
[0027] The electroplating time is set to 2 minutes, and the catalytic material in the electroplating solution is deposited on the surface of the carbon fiber that has undergone surface pretreatment, thereby completing the coating of the catalytic coating on the surface of the carbon fiber.
[0028] In an exemplary embodiment of the present disclosure, carbon-containing gas is used as a carbon source, the catalytic coating is used as a catalyst by chemical vapor deposition, and carbon nanotubes are grown on the surface of the carbon fiber, including:
[0029] The carbon fiber coated with a catalytic coating on the surface is placed in a tubular furnace, and connected to an argon gas path and a carbon-containing gas path;
[0030] The air in the tube furnace is removed by controlling the flow rate of argon gas to 0.5-0.7 liters per minute;
[0031] After the air in the tube furnace is exhausted, a temperature control program is started to adjust the nanotube growth temperature at a heating rate of 10 degrees Celsius per minute;
[0032] When the temperature inside the tube furnace reaches 450-550 degrees Celsius, a carbon-containing gas with a flow rate of 0.2-0.4 liters per minute and an argon gas with a flow rate of 0.5-0.7 liters per minute are simultaneously input into the tube furnace;
[0033] The temperature inside the tube furnace is maintained at 450-550 degrees Celsius, and the growth of carbon nanotubes is completed on the surface of the carbon fiber at a growth cycle of one minute.
[0034] In an exemplary embodiment of the present disclosure, it further includes:
[0035] Using deionized water to wash the carbon fiber after the surface pretreatment, and when the washing water solution is neutral, drying the carbon fiber after the surface pretreatment;
[0036] The carbon fiber coated with the catalytic coating is cleaned with deionized water, and when the cleaning water solution is neutral, the carbon fiber coated with the catalytic coating is dried;
[0037] The carbon nanotubes are washed with deionized water, and when the washing water solution is neutral, the carbon nanotubes are dried.
[0038] In one aspect of the present disclosure, a device for uniformly coating catalyst particles on the surface of a carbon fiber is provided, comprising:
[0039] The carbon fiber surface high temperature degumming module decomposes the glue remaining on the carbon fiber surface by heating the carbon fiber to a preset high temperature;
[0040] A carbon fiber surface activation module is used to perform surface activation treatment on the carbon fiber after the colloid is removed, thereby completing the pretreatment of the carbon fiber surface;
[0041] A catalytic coating module is used to pass current into a pre-configured electroplating solution to coat the surface of the carbon fiber that has undergone surface pretreatment with a catalytic coating;
[0042] The carbon nanotube growth module uses carbon-containing gas as a carbon source and uses the catalytic coating as a catalyst through a chemical vapor deposition method to complete the growth of carbon nanotubes on the surface of the carbon fiber.
[0043] A method for uniformly coating the surface of a carbon fiber with catalyst particles in an exemplary embodiment of the present disclosure includes, first, using a high-temperature degumming method, heating the carbon fiber to a preset high temperature to decompose the colloid remaining on the surface of the carbon fiber. Afterwards, the surface pretreatment of the carbon fiber is completed by performing a surface activation treatment on the carbon fiber after the colloid is removed using an electrochemical anodization method. Then, based on the electroplating method, an electric current is passed through a pre-configured electroplating solution to coat the surface of the carbon fiber that has undergone surface pretreatment with a catalytic coating. Finally, using a carbon-containing gas as a carbon source, the catalytic coating is used as a catalyst through a chemical vapor deposition method to complete the growth of carbon nanotubes on the surface of the carbon fiber. The disclosed embodiment achieves uniform distribution of catalyst particles on the surface of the carbon fiber to ensure that the carbon nanotubes can grow uniformly on the surface of the carbon fiber, thereby improving the accuracy and consistency of the carbon nanotube growth process.
[0044] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The above and other features and advantages of the present disclosure will become more apparent by describing in detail example embodiments thereof with reference to the attached drawings.
[0046] Figure 1 A flow chart showing a method for uniformly coating catalyst particles on a carbon fiber surface according to an exemplary embodiment of the present disclosure is shown;
[0047] Figure 2 A schematic diagram of SEM analysis of unoxidized carbon fiber in a method for uniformly coating catalyst particles on the surface of carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0048] Figure 3 A schematic diagram of SEM analysis of oxidized carbon fiber in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0049] Figure 4 A schematic diagram of FTIR analysis of oxidized carbon fiber in a method for uniformly coating catalyst particles on the surface of carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0050] Figure 5 A schematic diagram of XPS analysis of carbon fiber before anodization in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0051] Figure 6 A schematic diagram of XPS analysis of carbon fiber after anodic oxidation for 1 minute in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0052] Figure 7 A schematic diagram of XPS analysis of carbon fiber after 2 minutes of anodization in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0053] Figure 8 A schematic diagram of XPS analysis of carbon fiber after anodic oxidation for 3 minutes in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0054] Fig. 9 A schematic diagram of XPS analysis of carbon fiber after anodic oxidation for 4 minutes in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0055] Fig.10 A schematic diagram of XPS analysis of carbon fiber after 5 minutes of anodization in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0056] Fig.11A schematic diagram of XRD analysis of carbon fiber after anodization in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0057] Fig.12 A schematic diagram of Raman analysis of carbon fiber after anodization in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0058] Fig.13 A schematic diagram of SEM analysis of nickel-plated carbon fiber when the anodizing time is 3 minutes in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0059] Fig.14 A schematic diagram of EDS analysis of nickel-plated carbon fiber in a method for uniformly coating catalyst particles on the surface of a carbon fiber according to an exemplary embodiment of the present disclosure is shown;
[0060] Fig.15 A schematic block diagram of a device for uniformly coating catalyst particles on the surface of carbon fiber according to an exemplary embodiment of the present disclosure is shown. DETAILED DESCRIPTION
[0061] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this disclosure will be comprehensive and complete and will fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted.
[0062] In addition, the described features, structures or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced without one or more of the specific details, or other methods, components, materials, devices, steps, etc. may be adopted. In other cases, known structures, methods and devices, implementations, materials or operations are not shown or described in detail to avoid blurring the various aspects of the present disclosure.
[0063] The block diagrams shown in the accompanying drawings are merely functional entities and do not necessarily correspond to physically independent entities. That is, these functional entities may be implemented in software form, or these functional entities or parts of functional entities may be implemented in one or more software hardened modules, or these functional entities may be implemented in different networks and / or processor devices and / or microcontroller devices.
[0064] In this exemplary embodiment, a method for uniformly coating catalyst particles on the surface of a carbon fiber is first provided; Figure 1 As shown in , the method for uniformly coating catalyst particles on the surface of a carbon fiber may include the following steps:
[0065] Step S110, using a high temperature debonding method, the carbon fibers are heated to a preset high temperature to decompose the glue remaining on the surface of the carbon fibers.
[0066] Step S120, using an electrochemical anodizing method, the carbon fiber is subjected to surface activation treatment after the colloid is removed, thereby completing the pretreatment of the carbon fiber surface.
[0067] Step S130, based on the electroplating method, current is passed through a pre-configured electroplating solution to apply a catalytic coating to the surface of the carbon fiber that has undergone surface pretreatment.
[0068] Step S140, using carbon-containing gas as a carbon source, using the catalytic coating as a catalyst through chemical vapor deposition to complete the growth of carbon nanotubes on the surface of the carbon fiber.
[0069] A method for uniformly coating the surface of a carbon fiber with catalyst particles in an exemplary embodiment of the present disclosure includes, first, using a high-temperature degumming method, heating the carbon fiber to a preset high temperature to decompose the colloid remaining on the surface of the carbon fiber. Afterwards, the surface pretreatment of the carbon fiber is completed by performing a surface activation treatment on the carbon fiber after the colloid is removed using an electrochemical anodization method. Then, based on the electroplating method, an electric current is passed through a pre-configured electroplating solution to coat the surface of the carbon fiber that has undergone surface pretreatment with a catalytic coating. Finally, using a carbon-containing gas as a carbon source, the catalytic coating is used as a catalyst through a chemical vapor deposition method to complete the growth of carbon nanotubes on the surface of the carbon fiber. The disclosed embodiment achieves uniform distribution of catalyst particles on the surface of the carbon fiber to ensure that the carbon nanotubes can grow uniformly on the surface of the carbon fiber, thereby improving the accuracy and consistency of the carbon nanotube growth process.
[0070] Next, a method for uniformly coating the surface of carbon fibers with catalyst particles in this exemplary embodiment will be further described.
[0071] In the template configuration step S110, a high temperature debonding method may be used to decompose the glue remaining on the surface of the carbon fiber by heating the carbon fiber to a preset high temperature.
[0072] During the production process of carbon fiber, in order to prevent the carbon fiber from breaking, hairy, etc., it is usually necessary to use a sizing agent (usually epoxy resin) to sizing the carbon fiber, so that the produced carbon fiber is smoother and easier to use and store.
[0073] Therefore, a certain amount of sizing agent colloid will remain on the surface of the carbon fiber, and it needs to be desizing treated before the experiment of the embodiment of this example begins.
[0074] There are two commonly used degumming methods. One is the chemical impregnation method, which is to immerse the carbon fiber in a chemical solvent so that the residual colloid on its surface dissolves into the solvent, and then wash and dry it to obtain the degummed carbon fiber material. The other method is the high-temperature degumming method, which is to place the cut carbon fiber in a high-temperature sintering furnace, introduce an inert gas as a protective gas, and heat it to a certain temperature (generally 300°C and above) to decompose the residual colloid on its surface into gaseous substances and discharge it with the inert gas, thereby preparing the degummed carbon fiber. In comparison, the high-temperature degumming method is simpler and faster to operate, and has a higher surface colloid removal rate.
[0075] In a specific example, a high temperature sintering furnace is used to remove the binder from the carbon fiber. The specific process is as follows:
[0076] In the first step, the carbon fiber is cut into carbon fiber segments of about 15 cm in length to facilitate subsequent experiments.
[0077] The second step is to turn on the high temperature sintering furnace for preheating, adjust the intelligent temperature control instrument, set the degumming temperature to 400-500°C, preferably 450°C, the insulation time to 2 hours, and the heating rate to 10°C / min.
[0078] The third step is to load the cut carbon fiber segments into the sintering furnace, close the furnace, and connect the argon gas line.
[0079] The fourth step is to open the argon valve, adjust the outlet pressure of the argon valve to 0.1MPa, check the air tightness of the device, and control the argon flow rate to 0.4-0.6L / min through the flow meter.
[0080] The fifth step is to wait until the argon gas has exhausted the air in the furnace, start the temperature control program, and begin heating and degumming.
[0081] Step 6. After the temperature control program is completed, turn off the argon switch and take out the carbon fiber that has been debonded.
[0082] In the template configuration step S120, the electrochemical anodization method can be used to perform surface activation treatment on the carbon fiber after the colloid is removed, thereby completing the pretreatment of the carbon fiber surface.
[0083] In the embodiment of this example, after high-temperature carbonization treatment, the surface of the carbon fiber will show a certain chemical inertness and become very smooth, which greatly reduces its surface connectivity and physical adsorption. As a result, when the carbon fiber is composited with other materials, the interfacial bonding force between the carbon fiber and the composite material will be weakened, which is very unfavorable to the improvement of the performance of the composite material.
[0084] Therefore, it is necessary to use electrochemical anodization (the main reason for using electrochemical anodization is that, during the electrolysis of water, the anode will generate highly active new ecological oxygen, which will react with the carbon-carbon double bonds on the surface of the carbon fiber at the anode to generate oxygen-containing functional groups. At the same time, the current passing through will have a certain etching effect on the surface of the carbon fiber, increasing the roughness of the carbon fiber surface) to treat the surface of the carbon fiber in order to increase the activity of the carbon fiber surface and enhance its interfacial bonding strength after composite with other materials.
[0085] In a specific example, the carbon fiber segment after high temperature removal of colloid is used as the anode of the electrolytic cell, and the platinum electrode is used as the cathode. The distance between the two electrodes is 9-11 cm, preferably 10 cm. The electrolyte is a 5wt% diammonium phosphate solution (the specific configuration method of the electrolyte is to weigh 50g of diammonium phosphate solid medicine with an electronic balance and dissolve it in water. After the solid medicine is completely dissolved, slowly add water until the solution mass is 1000g).
[0086] Finally, a DC regulated power supply is used as the power supply of the electrolytic cell, and the power output mode is adjusted to the constant current mode, and the current is adjusted to 0.4-0.6A and the voltage is 15V-20V. The power-on time is set to 1 minute, 2 minutes, 3 minutes, 4 minutes, and 5 minutes respectively. After the setting is completed, the oxidation reaction of the carbon fiber is started.
[0087] In the embodiment of this example, the oxidized carbon fiber can be repeatedly washed with deionized water until the washed water solution is neutral, and then placed in a constant temperature drying oven at 80°C for 2 hours to obtain five groups of carbon fiber samples after electrochemical anodization.
[0088] In a specific example, the entire electrochemical anodization reaction process can also be subjected to SEM analysis, FTIR analysis, XPS analysis, XRD analysis, and Raman analysis to verify the feasibility of electrochemical anodization on the surface treatment of carbon fiber. The following conclusions are drawn: After the surface of the carbon fiber is electrochemically oxidized, the proportion of oxygen elements on the surface of the carbon fiber increases, and the number of carbon atoms with oxygen-containing functional groups and disordered arrangement increases, indicating that electrochemical anodization oxidizes the surface of the carbon fiber and produces a certain etching effect on the carbon fiber, and this effect becomes more obvious as the oxidation time increases.
[0089] Among them, Figure 2-Figure 3As shown in the figure, after SEM analysis (Scanning Electron Microscope analysis), the surface of the carbon fiber that has not been electrochemically anodized is relatively smooth and flat, and there are no obvious defects on the surface. However, the surface of the carbon fiber that has been anodized can be seen to have obvious uneven areas. It can be seen that the current can etch the surface of the carbon fiber and cause the surface of the carbon fiber to be rough and uneven, making it easier for the catalyst ions to deposit on the surface of the carbon fiber.
[0090] like Figure 4 As shown, the analysis of the electrochemically anodized carbon fiber using FTIR (Fourier Transform Infrared Spectroscopy) shows that there are mainly four obvious absorption peaks. The absorption peak of -OH appears between 3200cm-1 and 3500cm-1, the infrared absorption peak of -CH3 appears between 3000cm-1 and 3250cm-1, the absorption peak of -C=O appears between 1600cm-1 and 1700cm-1, and the infrared absorption peak of -COC appears between 1300cm-1 and 1450cm-1. This shows that after electrochemical anodization, a certain amount of oxygen-containing functional groups are generated on the surface of the carbon fiber, which increases the surface activity of the carbon fiber and effectively improves the surface properties of the carbon fiber.
[0091] By analyzing the carbon fiber material before and after electrochemical anodization by XPS (X-ray Photoelectron Spectroscopy), we can know the element composition and content of the carbon fiber material surface. Figure 5-Figure 10 As shown in the figure, characteristic peaks representing C1s and O1s appear at 284.6eV and 531.4eV, indicating that the surface of the carbon fiber before and after electrochemical anodization mainly contains two elements, carbon and oxygen. It can be seen from the figure that after electrochemical anodization, the O1s peak increases and the Cls peak decreases, and this trend becomes more obvious with the increase of oxidation time, indicating that the oxidation treatment increases the proportion of oxygen element content on the carbon fiber surface and reduces the proportion of carbon element, which shows that the surface activity of the carbon fiber surface is effectively improved after electrochemical anodization.
[0092] XRD analysis (-ray Diffraction, X-ray diffraction analysis) of carbon fiber before and after electrochemical anodization can show the changes in the surface microstructure of carbon fiber. Fig.11As shown in the figure, all carbon fiber samples have characteristic peaks of graphite structure characterizing the carbon fiber crystal plane between 2 equals 25° and 26°. And with the continuous increase of oxidation time, the peak height of this type of characteristic peak is constantly decreasing, the peak width is constantly increasing, and the peak shape is gradually becoming flat from sharp. This shows that the surface graphitization structure of carbon fiber has changed with electrochemical anodization, and the longer the oxidation time, the more obvious this change is.
[0093] The Raman analysis method (Raman Spectroscopy) is used to analyze the surface of carbon fibers after electrochemical anodization to characterize the degree of disorder of carbon atoms on the surface of carbon fibers. Fig.12 As shown in the figure, two peaks appear. The first peak represents the D peak of disordered carbon atoms on the carbon fiber surface, and the second peak represents the G peak of ideal graphite lattice on the carbon fiber surface. The relative intensity of the two is represented by R value (R = IG / ID). The R value in the figure decreases with the increase of oxidation time, indicating that the content of disordered carbon atoms on the carbon fiber surface increases, indicating that electrochemical anodic oxidation has a certain etching effect on the carbon fiber surface, which increases the roughness of the carbon fiber surface. And as the oxidation time increases, the etching effect becomes more obvious.
[0094] In the template configuration step S130, an electric current may be passed through a pre-configured electroplating solution based on an electroplating method to apply a catalytic coating to the surface of the carbon fiber that has been surface pretreated.
[0095] In the embodiment of this example, before electroplating the carbon fiber, a plating solution is prepared, and the plating solution formula is: 260-280 grams per liter of nickel sulfate hexahydrate, 65-75 grams per liter of nickel chloride, 35-45 grams per liter of boric acid and 0.09-0.11 grams per liter of sodium dodecyl sulfate. The preferred solution can use the formula: main salt NiSO4·6H2O 270g / L, activator NiCl 70g / L, buffer H3BO340g / L, sizing agent sodium dodecyl sulfate 0.1g / L.
[0096] The specific steps are as follows: first, 270g of nickel sulfate hexahydrate, 70g of nickel chloride, 40g of boric acid, and 0.1g of sodium dodecyl sulfate solid medicine are weighed respectively using an electronic balance. Then, two cups of 500g of pure water are taken in beakers respectively, and nickel sulfate hexahydrate and nickel chloride are dissolved in one cup, and boric acid is dissolved in another cup of pure water. After all the solid medicines are dissolved, the two cups of solution are stirred and mixed evenly. Finally, sodium dodecyl sulfate is added, stirred and mixed thoroughly, and the pH value (acid-base value) of the electroplating solution is controlled between 3 and 4, and the nickel electroplating solution can be obtained.
[0097] After the plating solution is prepared, a DC regulated power supply is used as the power supply for electroplating, and the output mode is set to constant current mode, the current intensity is adjusted to 0.3-0.5A, and the voltage is adjusted to 17V-20V. The electroplating temperature is room temperature, and the electroplating time is controlled within 2 minutes.
[0098] Then, the carbon fiber after electrochemical anodization is used as the cathode, and the platinum electrode is used as the anode, and the distance between the two electrodes is 9-11 cm, preferably 10 cm. Then, the surface of the carbon fiber is nickel plated.
[0099] In the embodiment of this example, the electroplated carbon fiber can also be repeatedly rinsed with deionized water to remove the residual solution on the surface until the solution washed with water becomes neutral, and then placed in a constant temperature drying oven at 100°C for 2 hours to obtain carbon fiber with nickel plating on the surface.
[0100] In a specific example, the entire electroplating process can also be subjected to SEM analysis, EDS analysis, XPS analysis, and XRD analysis to verify the feasibility of electrochemical anodizing reaction for carbon fiber surface treatment. The following conclusions are drawn: Fig.13 As shown, through the study of nickel electroplating on the surface of carbon fiber, it can be observed by scanning electron microscopy that the nickel plating on the surface of the carbon fiber after 3 minutes of oxidation treatment is the most uniform, and it is found that the longer the oxidation time, the more nickel is plated.
[0101] The difference from the above step S120 is that it is necessary to perform elemental composition analysis on the surface of the electroplated carbon fiber, such as Fig.14 As shown, EDS analysis (Energy Dispersive X-ray Spectroscopy) of the carbon fiber surface after electroplating shows that the surface of the nickel-plated carbon fiber mainly contains three elements: C, O, and Ni, indicating that no other impurity elements are introduced during electroplating and the coating is metallic nickel.
[0102] In the template configuration step S140, carbon-containing gas (such as methane, acetylene, ethylene, etc.) can be used as a carbon source, and the catalytic coating can be used as a catalyst through chemical vapor deposition to complete the growth of carbon nanotubes on the surface of the carbon fiber.
[0103] In the embodiment of this example, the main reason for selecting chemical vapor deposition to prepare carbon nanotubes and carbon fiber composite materials is that chemical vapor deposition is simple to operate, the grown carbon nanotubes are of high purity, and are suitable for large-scale production applications.
[0104] In a specific example, the specific steps of preparing carbon nanotube and carbon fiber composite materials by chemical vapor deposition are as follows:
[0105] The first step is to turn on the power switch of the tube furnace to preheat the equipment, load the electroplated carbon fiber onto the quartz boat, and place it into the furnace of the tube furnace.
[0106] The second step is to connect the argon gas line and the carbon-containing gas line, check the air tightness of the experimental equipment, and adjust the flow rate of the flow meter.
[0107] The third step is to set the intelligent temperature control program of the tube furnace, set the heating rate to 10°C / min, the carbon nanotube growth temperature to 450-550°C, preferably 500°C, and the insulation time to 1 hour.
[0108] The fourth step is to introduce argon gas at a flow rate of 0.5-0.7L / min to exhaust the air in the furnace and also serve as a protective gas to prevent carbon fiber oxidation.
[0109] The fifth step is to start the temperature control program and begin to increase the temperature in the furnace. After reaching the predetermined temperature, open the carbon-containing gas flow switch and pass a carbon-containing gas (acetylene is used as the carbon-containing gas in this example) with a flow rate of 0.2-0.4L / min. At the same time, keep the argon gas flowing continuously. It should be noted that the flow ratio of acetylene to argon is controlled to be 0.3:0.6 (in L / min).
[0110] Step 6. After the set carbon nanotube growth time of 1 minute is reached, turn off the acetylene flow switch, but keep the argon gas flowing throughout the process. After the furnace is completely cooled, turn off the argon switch, take out the carbon fiber, and observe the growth of carbon nanotubes on the surface of the carbon fiber.
[0111] In the embodiment of this example, the carbon nanotubes may be repeatedly washed with deionized water until the washed water solution is neutral, and then placed in a constant temperature drying oven at 80° C. for 2 hours to obtain a carbon nanotube sample.
[0112] It should be noted that, although the steps of the method in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0113] In addition, in this exemplary embodiment, a device for uniformly coating the surface of carbon fibers with catalyst particles is also provided. Fig.15 As shown, the device 400 for uniformly coating catalyst particles on the surface of carbon fiber may include: a carbon fiber surface high temperature degumming module 410, a carbon fiber surface activation module 420, a catalytic coating module 430 and a carbon nanotube growth module 440. Among them:
[0114] The carbon fiber surface high temperature degumming module 410 decomposes the colloid remaining on the carbon fiber surface by heating the carbon fiber to a preset high temperature;
[0115] The carbon fiber surface activation module 420 performs surface activation treatment on the carbon fiber after the colloid is removed, thereby completing the pretreatment of the carbon fiber surface;
[0116] The catalytic coating module 430 is configured to pass current into a pre-configured electroplating solution to coat the surface of the carbon fiber that has undergone surface pretreatment with a catalytic coating;
[0117] The carbon nanotube growth module 440 uses the carbon-containing gas as a carbon source and uses the catalytic coating as a catalyst through chemical vapor deposition to complete the growth of carbon nanotubes on the surface of the carbon fiber.
[0118] The specific details of each of the above-mentioned device modules for uniformly coating catalyst particles on the surface of carbon fibers have been described in detail in the corresponding method for uniformly coating catalyst particles on the surface of carbon fibers, and will not be repeated here.
[0119] It should be noted that, although several modules or units of a device 400 for uniformly coating catalyst particles on a carbon fiber surface are mentioned in the above detailed description, such division is not mandatory. In fact, according to an embodiment of the present disclosure, the features and functions of two or more modules or units described above can be embodied in one module or unit. Conversely, the features and functions of one module or unit described above can be further divided into multiple modules or units to be embodied.
[0120] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to an exemplary embodiment of the present invention, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0121] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary technical means in the art that are not disclosed in the present disclosure. The specification and examples are to be considered as exemplary only, and the true scope and spirit of the present disclosure are indicated by the claims.
[0122] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for uniformly coating catalyst particles on the surface of carbon fiber, characterized in that: include: Use high temperature debonding method to decompose the glue remaining on the surface of carbon fiber by heating the carbon fiber to a preset high temperature; The surface of the carbon fiber is pretreated by performing a surface activation treatment on the carbon fiber after the colloid is removed using an electrochemical anodizing method; Based on the electroplating method, current is passed through a pre-configured electroplating solution to coat the surface of the carbon fiber that has undergone surface pretreatment with a catalytic coating; The carbon-containing gas is used as a carbon source, and the catalytic coating is used as a catalyst through a chemical vapor deposition method to complete the growth of carbon nanotubes on the surface of the carbon fiber.
2. The method according to claim 1, characterized in that The preset high temperature is 400-500 degrees Celsius.
3. The method according to claim 2, characterized in that By heating the carbon fiber to a preset high temperature, the colloid remaining on the fiber surface is decomposed, including: Load the carbon fiber into a high-temperature sintering furnace and connect it to an argon gas line; Expelling air from the high temperature sintering furnace by controlling the flow rate of argon gas to 0.4-0.6 liters per minute; After the air in the high-temperature sintering furnace is exhausted, the temperature control program is started to adjust the debonding temperature to 400-500 degrees Celsius at a heating rate of 10 degrees Celsius per minute, and the temperature of 400-500 degrees Celsius is maintained for two hours, and the glue remaining on the surface of the carbon fiber is started to be decomposed.
4. The method according to claim 1, characterized in that: The carbon fiber after the colloid is removed is subjected to surface activation treatment, comprising: A 5% by mass ammonium dihydrogen phosphate solution is prepared as an electrolyte; A DC regulated power supply with a current of 0.4A-0.6A and a voltage of 15V-20V is used as the power supply for the electrolytic cell; The carbon fiber after the colloid is removed is set as the anode of the electrolytic cell, the platinum electrode is set as the cathode of the electrolytic cell, and the electrode distance is 9-11 cm; The electrolysis time was set to 1 minute, and the electrolysis pretreatment of the carbon fiber surface was started.
5. The method according to claim 1, characterized in that The components of the electroplating solution include nickel sulfate hexahydrate with a mass concentration of 260-280 grams per liter, nickel chloride with a mass concentration of 65-75 grams per liter, boric acid with a mass concentration of 35-45 grams per liter, and sodium dodecyl sulfate with a mass concentration of 0.09-0.11 grams per liter.
6. The method according to claim 5, characterized in that The pH value of the electroplating solution is 3-4.
7. The method according to claim 5, characterized in that Passing current into a pre-configured electroplating solution to apply a catalytic coating to the surface of the carbon fiber that has undergone surface pretreatment, comprising: A DC regulated power supply with a current of 0.3A-0.5A and a voltage of 17V-20V is used as an electroplating power supply; The carbon fiber with surface pretreatment is set as the electroplating cathode, the platinum electrode is set as the electroplating anode, and the electrode distance is 9-11 cm; The electroplating time is set to 2 minutes, and the catalytic material in the electroplating solution is deposited on the surface of the carbon fiber that has undergone surface pretreatment, thereby completing the coating of the catalytic coating on the surface of the carbon fiber.
8. The method according to claim 1, characterized in that The carbon-containing gas is used as a carbon source, and the catalytic coating is used as a catalyst by chemical vapor deposition to complete the growth of carbon nanotubes on the surface of the carbon fiber, including: The carbon fiber coated with a catalytic coating on the surface is placed in a tubular furnace, and connected to an argon gas path and a carbon-containing gas path; The air in the tube furnace is removed by controlling the flow rate of argon gas to 0.5-0.7 liters per minute; After the air in the tube furnace is exhausted, a temperature control program is started to adjust the nanotube growth temperature at a heating rate of 10 degrees Celsius per minute; When the temperature inside the tube furnace reaches 450-550 degrees Celsius, a carbon-containing gas with a flow rate of 0.2-0.4 liters per minute and an argon gas with a flow rate of 0.5-0.7 liters per minute are simultaneously input into the tube furnace; The temperature inside the tube furnace is maintained at 450-550 degrees Celsius, and the growth of carbon nanotubes is completed on the surface of the carbon fiber at a growth cycle of one minute.
9. The method according to any one of claims 4, 7 and 8, characterized in that: Also includes: Using deionized water to wash the carbon fiber after the surface pretreatment, and when the washing water solution is neutral, drying the carbon fiber after the surface pretreatment; The carbon fiber coated with the catalytic coating is cleaned with deionized water, and when the cleaning water solution is neutral, the carbon fiber coated with the catalytic coating is dried; The carbon nanotubes are washed with deionized water, and when the washing water solution is neutral, the carbon nanotubes are dried.
10. A device for uniformly coating catalyst particles on the surface of carbon fiber, characterized in that: include: The carbon fiber surface high temperature degumming module decomposes the glue remaining on the carbon fiber surface by heating the carbon fiber to a preset high temperature; A carbon fiber surface activation module is used to perform surface activation treatment on the carbon fiber after the colloid is removed, thereby completing the surface pretreatment of the carbon fiber; A catalytic coating module is used to pass current into a pre-configured electroplating solution to coat the surface of the carbon fiber that has undergone surface pretreatment with a catalytic coating; The carbon nanotube growth module uses carbon-containing gas as a carbon source and uses the catalytic coating as a catalyst through a chemical vapor deposition method to complete the growth of carbon nanotubes on the surface of the carbon fiber.